Development of an evaluation indicator system for the rational use of proton pump inhibitors in pediatric intensive care units: An application of Delphi method. Issue 24 (18th June 2021) - Ni, Xiaofeng; Lin, Mao; Li, Jialian; Zeng, Linan; Li, Wenrui; Huang, Liang; Li, Deyuan; Zhang, Lingli
Abstract : Abstract: Proton pump inhibitors are frequently used to prevent gastrointestinal bleeding in critically ill patients. But there is little information in the instructions about the usages for children. It is important to monitor the appropriate use of proton pump inhibitors, especially in pediatrics. Therefore, we developed an evaluation indicator system for the rational use of proton pump inhibitors in pediatric intensive care units. First, a systematic review was conducted to developed the initial indicators. Then 2 rounds of Delphi surveys were conducted to collecting opinions from a panel of independent experts, and the indicator system was modified to form the final indicators according to the opinions. Finally, the analytic hierarchy procedure was used to determine the weight of each indicator. A total of 6 guidelines and 2 studies met the inclusion and exclusion criteria. Based on literature and discussion among experts, an initial indicator system including 4 first-rank indicators and 12 second-rank indicators was formed. After 2 rounds of Delphi surveys, 2 indicators were added, 5 indicators were deleted, and 1 indicator was revised, so the final indicator system contained a total of 13 indicators including 3 first-rank indicators (drug selection, drug usage and dosage, duration of drug therapy) and 10 second-rank indicators (the proportion of PPIs used in children, children under 1 year old, children who is using glucocorticoids, children with nonsteroidal anti-inflammatory drugs, children with gastroesophageal reflux disease, children with sepsis, children with ventilators in PICU; the strength of PPIs' use, the proportion of omeprazole in children using PPIs during the same period; the average days of PPIs used in children). By analyzing scores, all coefficients met the standard, indicating the indicators were scientific and credible. Through a two-round Delphi survey, 3 first-rank indicators and ten second-rank indicators were developed, which will help drug administrative departments to promote the rational use of PPIs for children in PICUs. What is more, our study can constitute a methodological reference for the development of other indicator systems.